Expert System to Diagnose Angina Pectoris Disease (Sitting Wind) Using the Naïve Bayes Method - Intan Diba Aulia Sari; Herlina Latipa Sari; Juju Jumadi (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2023)
aspects of data or information. The issue of security and confidentiality of computer data is something that is important in this information era, especially for the Teluk Segara Sub-District Office, Bengkulu City. Various ways are done to protect the data or information. One of them is by using cryptography with the Rail Fence Cipher algorithm. The Rail Fence Cipher algorithm applies the tranposition technique by arranging the plaintext in the matrix in rows. The system implementation uses PHP programming language with MySql database. The method used in this research is waterfall, this application is designed using UML (Unified Modeling Language). From the analysis and discussion of the research obtained that the encryption results produced by Rail Fence Cipher do not change the plaintext results into ciphertext if the key is greater or more than the plaintext character.